Assessing urine ammonium concentration by urine osmolal gap in chronic kidney disease. Issue 10 (20th July 2021) - Fujimaru, Takuya; Shuo, Takuya; Nagahama, Masahiko; Taki, Fumika; Nakayama, Masaaki; Komatsu, Yasuhiro
Abstract: Acidemia is one of the risk factors for end‐stage kidney disease and increases the mortality rate of patients with chronic kidney disease (CKD). Although urinary ammonium (U‐NH4 + ) is the crucial component of renal acid excretion, U‐NH4 + concentration is not routinely measured. To estimate U‐NH4 +, urine osmolal gap (UOG = urine osmolality − [2(Na + + K + ) + urea + glucose]) is calculated and the formula (U‐NH4 +  = UOG/2) has traditionally been used. However, the usefulness of this formula is controversial in CKD patients. We assessed the relationship between U‐NH4 + and UOG in patients with CKD. Blood and spot urine samples were collected in 36 patients who had non‐dialysis‐dependent CKD. The mean ±  SD age of patients was 72.0 ± 14.8 years, and the mean ±  SD serum creatinine and U‐NH4 + were 2.7 ± 2.3 mg/dl and 9.3 ± 9.2 mmol/L, respectively. A significant relationship was found between UOG/2 and U‐NH4 + ( r  = .925, p  < .0001). U‐NH4 + estimated using the UOG was on average higher by 4.7 mmol/L than the measured one. Our results suggested that UOG could be a useful tool in clinical settings, especially in patients with moderate to severe CKD. SUMMARY AT A GLANCE: The significance of the urinary osmolality gap (UOG) in estimating urinary ammonium levels (U‐NH4 + ) in CKD patients is investigated and it was found U‐NH4 + is important in detecting subclinical acidosis and tubular dysfunction. Hence, UOG is useful in the management of patients with moderate to severe CKD.